Toxicity of conventonal insecticides to fourth instar larvae of tobaccocaterpillar, Spodoptera litura (Fab.) in different generations - Ahmad, Irshad; Ahad, Ishtiyaq; Gupta, R K; Monobrullah, Mohd; Bhagat, R M; Ahmad, Hafeez (Journal of Phytology, 2011)
Studies on development of resistance in tobacco caterpillar against some insecticides were carried out in the laboratory, Division of Entomology, Udheywalla, Jammu. The differential susceptibility level of parental and susceptible strains of tobacco caterpillar to conventional insecticides revealed that the level of susceptibility in 4th instar larvae of this insect has decreased considerably in parental strain as compared to recommended concentrations of insecticides. The highest resistance factor of 9.33 was observed with monocrotophos whereas malathion encountered lowest resistance factor of 1.50. Comparison of the LC50 values obtained in succeeding generations with the 1st generation in 4th instar larvae of S. litura revealed that the resistance developed in an increasing order in all the six generations. The resistance ratio in the 6th generation as compared to the 1st generation was 3.97- fold in endosulfan, 3.11 in malathion and 3.45 in carbaryl.